The impact of the infodemic on the stock market under the COVID-19: taking the investors’ information infection index as the intermediary variable - Xie, Wanying; Tang, Yuzhu; Xu, Zeshui; Zhang, Xu; Lai, Dengling (Technological and Economic Development of Economy, 2023)
The outbreak of COVID-19 is synchronized with the outbreak of the infodemic, which directly affected the sentiment and behaviours of investors and thus affected the stock market. At the same time, the outbreak of the infodemic has led to the information infection of the public. With the information infection, panic, anxiety, and other emotions have spread among the public, affecting the behaviours of investors, and thus affecting the stock returns. This paper explores the impact of the infodemic on the stock market by selecting keywords related to the “epidemic situation”, using the Baidu information index as an indicator to measure the infodemic, and the Baidu search index as an indicator to measure the degree of information infection. The empirical findings reveal that: First, the more serious the infodemic, the more severe the information infection; Second, the deeper the infodemic, the lower the stock returns of A-share listed companies; Third, there is a phenomenon that the infodemic affects the stock returns through the intermediary of information infection in the stock market. First published online 20 February 2023